The Relationship between Constructivist Thinking and Academic Engagement among University Students in Light of Some Variables - Mohamad Mostfa Egbaria (European Scientific Journal, ESJ, 2024)
This paper focuses on revealing the relationship between constructivist thinking and academic engagement among university students in light of some variables. To achieve the objectives, a sample of 697 male and female students was selected using available sample method at the Qasimi Academic College of Education. The correlational approach was used. The constructive thinking scale and measure of academic participation were applied. The results showed a statistically significant positive correlation between academic participation and constructive thinking dimensions. The results also showed a statistically significant negative correlation between academic participation and destructive constructive thinking dimensions. The results indicated that there were no significant differences in correlation factors between constructive thinking and academic engagement attributed to gender and specialization. Based on the findings, it is logical to conclude that the increase in constructive dimensions of constructive thinking contributes to achieving academic engagement, while the increase in destructive dimensions of constructive thinking reduces academic engagement.